2023
DOI: 10.3389/fpsyg.2023.1131896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived supervisor support and leader-member exchange on employees’ intention to leave in public sector museums: A parallel mediation approach

Abstract: High staff turnover in certain public sector organizations in Pakistan is a challenging problem, and organizations strive to reduce this issue using different mechanisms. Therefore, this research investigates the parallel mediation impact of perceived organizational support (POS) and organizational citizenship behavior (OCB) on the relationships among perceived supervisor support (PSS), leader-member exchange (LMX), and employee’s intention to leave (IL). Data were collected from 482 employees working in publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Subsequently, the COVID-19 pandemic introduced additional stressors in terms of adapting to online teaching, managing hybrid classrooms, and addressing the emotional needs of students (Poon, 2021). Conversely, the study of Asif et al (2023) in Pakistan found that teachers' job satisfaction positively correlates with perceived supervisor support and trust. This finding underscores the importance of positive relationships between teachers and their supervisors in promoting job satisfaction among secondary school teachers.…”
Section: Introductionmentioning
confidence: 88%
“…Subsequently, the COVID-19 pandemic introduced additional stressors in terms of adapting to online teaching, managing hybrid classrooms, and addressing the emotional needs of students (Poon, 2021). Conversely, the study of Asif et al (2023) in Pakistan found that teachers' job satisfaction positively correlates with perceived supervisor support and trust. This finding underscores the importance of positive relationships between teachers and their supervisors in promoting job satisfaction among secondary school teachers.…”
Section: Introductionmentioning
confidence: 88%
“…Second, the common method factor was added to the hypothesized four-factor model (Baseline Model 1), giving a new CMV model. All scale items were loaded into a common method factor and specified to correlate with other substantive latent factors [62,63]. The results come through the CMV model seem to be a good fit (χ 2 (509) = 1028.19, CFI = 0.95, TLI = 0.94, RMSEA = 0.05, SRMR = 0.09).…”
Section: Assessment Of CMVmentioning
confidence: 98%
“…It plays a substantial role in drawing in customers, devising tactics for indigenous growth, and tourism facilities promised in the marketplace. Moreover, satisfaction is vital to successful destination marketing as well as a tourist service organizations [27]. Agyeiwaah, et al [28] and Chen and Chen [29] defined the feelings of displeasure regarding travelers as a sign of dissatisfaction, while travelers who enjoyed visiting were satisfied; therefore, tourist contentment is a considerable factor for tourists in deciding to visit the tourist spots again and again.…”
Section: Tourist Satisfaction (Ts)mentioning
confidence: 99%